PENYUSUNAN JOB ANALYSIS DAN SOSIALISASINYA PADA DD CONSULTANT - Iwan, Yumin (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
Nowadays, consultant organizations are more and more needed, which have impact on the development of DD consultant, as a consultant organization in Surabaya city. The development of the company should be followed by stabilization of the organization internal system. The purpose of this research is to assist the development of the company through the development of job analysis system and its socialization. Research assessment indicate uncertainty about employees job, overlapping task, lack of understanding about authority possessed, as well as sense of anxiety among employees related to work activity in DD consultant. Therefore, as an intervention, researcher will make job analysis which divided into job description and job specification, together with socialization design for job analysis itself.